High Genetic Diversity and Gene Flow among Cultured and Wild Populations of Bighead Catfish (Clarias macrocephalus) in the Mekong Delta of Viet Nam Inferred from ISSR Markers - Nguyen, Ngoc-Tran Thi Nguyen; Duong, Thuy-Yen (Journal of Fisheries and Environment, 2022)
Bighead catfish (Clarias macrocephalus) is an important aquaculture species in the Mekong Delta of Viet Nam, but its farming has been facing such difficulties as slow growth and low seed quality. To apply genetic improvement programs to enhance farming production, it is crucial to start with a base population with high genetic diversity. This study compared genetic diversity between cultured and wild bighead catfish populations using inter-simple sequence repeat (ISSR) markers. Samples were collected in the Mekong Delta from two cultured populations (in Can Tho and Long An provinces) and two wild populations (in Ca Mau and Hau Giang). A total of 112 individuals was screened using six highly polymorphic ISSR primers which generated 61 scorable bands (500-3,000 bp). The study found that levels of genetic diversity of bighead catfish populations were high, with the number of effective alleles from 1.42 to 1.50, Shannon Index from 0.381 to 0.433, and unbiased expected heterozygosity from 0.257 to 0.297; those values from cultured populations were lower than wild populations. Moreover, the value of Nei’s unbiased genetic distance among populations was low, indicating high gene flow among bighead catfish populations distributed in the Mekong Delta, Viet Nam.